Optimizing Deep Learning: Workshop on Improving Teacher Capacity in the Application of Artificial Inteligent (AI) and Coding at SDIT Mafatih - Suzuki Syofian; Andi Susilo; Yan Sofyan Andhana Saputra; Aji Setiawan; Afri Yudha (Fakultas Teknik Universitas Darma Persada, 2026)
The integration of Coding and Artificial Intelligence (AI) in elementary education faces significant challenges, particularly regarding teacher readiness and infrastructure. SDIT Mafatih teachers often perceive Computational Thinking (CT) solely as a programming activity, overlooking its core pillars: decomposition, pattern recognition, abstraction, and algorithms. This community service program aims to enhance teacher capacity at SDIT Mafatih through a structured four-stage approach: a basic CT workshop emphasizing unplugged activities, provision of basic digital infrastructure, development of an integrative curriculum guide, and progressive Scratch training. The program utilized a participatory method involving 23 participants, supported by the provision of tablets and projectors. Results indicated a significant improvement in teacher competency, with average initial knowledge scores reaching 79.9% of the maximum. The activities successfully produced integrative lesson plans and digital learning modules, demonstrating an effective model for digital transformation in resource-limited educational settings.